Peran Mahasiswa Uinfas dalam Mengembangkan Sikap Toleransi Sejak Usia Sekolah Dasar dalam Program Kuliah Kerja Nyata (KKN) Tematik di RT 19 Bumi Ayu Kota Bengkulu - Seri Ulandari; Elsa Safitri; Cica Aries; Ovi Sesilia Pebrina; Asraf Yazid; Aam Amaliyah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This study aims to examine the role of UIN Fatmawati Sukarno Bengkulu students in fostering an attitude of tolerance among primary school-aged children in RT 19, Bengkulu City. Mutual respect is a crucial societal value that needs to be instilled early on to create an environment characterized by harmony, tolerance, and mutual regard. The study employs a qualitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentation. The research subjects include university students, primary school-aged children, and the local community of RT 19, Bengkulu City. The findings indicate that the students play a significant role in instilling mutual respect through educational activities, social engagement, educational games, and by modeling positive behavior for the children. These activities successfully enhance tolerance, cooperation, and social awareness among the primary school-aged children. Furthermore, support from the community and the local environment contributes to the success of the students’ initiatives. Thus, the students’ efforts to foster mutual respect from an early age positively impact the character development of children within the community. This study is expected to serve as a reference for the development of character education and community service activities in social settings.